PELAKSANAAN PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PENCURIAN PEMBERATAN - Meinecky, Ryan; Kadaryanto, Bagio; Pardede, Rudi (LPPM STIH Awang Long, 2025)
Qualified Theft refers to theft committed under certain circumstances or using specific methods that make the crime more severe, and therefore subject to harsher penalties than ordinary theft. This involves two or more individuals collaborating in the act of theft, such as jointly taking possessions. The purpose of this research is to analyze the Implementation of Law Enforcement Against the Crime of Qualified Theft in the Jurisdiction of Pekanbaru, to examine the obstacles in its enforcement, and to explore efforts to overcome those obstacles. The method used is sociological legal research. Based on the findings, law enforcement against the crime of qualified theft in Pekanbaru has not been optimally implemented. This is evident from the continued prevalence of aggravated theft cases, such as motorcycle theft, house and business burglaries, and theft from public facilities—often occurring repeatedly and in close timeframes. The high frequency of such crimes reflects a gap between legal enforcement efforts and the reality of criminal activity in the field. Obstacles to effective law enforcement include: Limited human resources compared to the volume of incoming reports each day, The socio-economic background of offenders—typically from lower-income groups with limited education, A lack of strong evidence and minimal technological support in the evidence-gathering process, Social interference from the perpetrator’s environment, including familial pressure on victims to withdraw their reports. Efforts to overcome these challenges involve: Improving the quality of investigations by strengthening human resources and applying digital technology, Enhancing police-community partnerships through initiatives like neighborhood-based police officers, legal education, and community empowerment via communication and coordination forums (FKPM), Optimizing cross-functional coordination and expediting case handling based on the principles of professionalism and proportionality, Reinforcing scientific investigation techniques such as detailed crime scene processing, forensic evidence collection, and utilizing CCTV footage and digital forensics as supporting evidence.